An evaluation of a unified practice assessment document for student nurses: Students’, mentors’ and academics’ views and experiences - Baillie, Lesley; Fish, Jane (The Journal of Practice Teaching and Learning, 2021)
Assessment of students’ performance in practice is an essential part of a health and social care education programme. In the United Kingdom, most nursing practice assessment documentation is specific to each university, leading to concerns about consistency. This paper’s aim is to present the development and evaluation of a unified practice assessment document. Nine London universities worked collaboratively with stakeholders to develop a pan-London practice assessment document, which aimed to increase consistency and quality of practice assessment. The evaluation aimed to investigate the views of nursing students, mentors and academics regarding implementation and use of the document in practice. Focus groups were conducted with students (n=46 in 6 groups), mentors (n=46 in 7 groups) and academic staff (n=42 in 6 groups) and the data were analysed using the framework approach. Four themes are presented: a robust and consistent approach; assessing professional values; essential skills acquisition; service user involvement. The new document was considered to foster consistency, reduce confusion and workload for mentors, and promote standardisation for practice assessment of student nurses across London.